Peran Dakwah Dalam Menyadarkan Pentingnya Bersikap Prososial Bagi Masyarakat Medan Maimun - Ahmad Sakban Wahyudi; Angga Purnama; Jacky Raihanta Barus; Surya Adrian Pangestu; Zidan Syahira; Zikri Ramadhani (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study aims to delve into the role of dakwah in educating the community of Medan Maimun about the importance of behaving prosocially in daily life. With a focus on cultural dakwah, this research uses a qualitative approach and case studies to explore how dakwah can strengthen Islamic values and promote prosocial behavior amidst diverse social dynamics. Through descriptive field data analysis, this study reveals the close relationship between dakwah, cultural diversity, and social cohesion in the context of the Medan Maimun community.The results of this research are expected to provide deeper insights into how dakwah can be an important instrument in building an inclusive, tolerant, and harmonious community. By reinforcing understanding of positive values and Islamic ethics, dakwah not only strengthens the religious identity of the community but also expands its scope in building mental and social well-being. This research makes a significant contribution to understanding the role of dakwah in promoting prosocial attitudes and strengthening social cohesion in a heterogeneous society.